ANALYSIS OF RADIOACTIVE DAMAGE TO SURFACES AND INDIVIDUALS - Khujaqulov, A.Kh. (Innovative Development in Educational Activities, 2023)
In the following article it is described about the adopted law on radiation conditions and their safety, nuclear explosion products rise to the troposphere and stratosphere, and then gradually fall to the surface forming precipitates of the earth in the latitude of the region where the nuclear explosion occurred.